(untitled) (Global Journal of Management and Business Research, 2019)
The paper investigates the best fit estimation technique for modeling volatility persistence in price of wheat. It further evaluates the source of rising volatility. It provides two main innovations: first, it analyzes wheat returns volatility types namely idiosyncratic and systematic volatility types and provides evidence of structural shifts in the price of wheat using the Narayan and Popp (2010) test and further modified the estimations to include both symmetric and asymmetric volatility models. Second, it uses several GARCH specifications to ascertain which of the sources of volatility generate more volatility. The paper finds two structural breaks that occur in 2015/2016 and 2018. It notices the existence of persistence and leverage effects in the returns volatility of wheat and that rising volatility regardless of types, necessitates demand for higher returns by investors to hold the investment. Conclusively, it recommends that, when modeling wheat return volatility, issues of asymmetric effects, structural shifts, and volatility persistence are very pertinent and that investors should structure investment portfolio with the knowledge that the idiosyncratic source heralds more persistence in volatility and therefore, necessitates utmost concentration.